1996
DOI: 10.1002/1097-0045(199609)29:3<153::aid-pros2990290303>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Codon 877 Mutation in the Androgen Receptor Gene in Advanced Prostate Cancer: Relation to Antiandrogen Withdrawal Syndrome

Abstract: The growth of prostate cancer is androgen responsive, and androgen receptor (AR) is thought to play an important role in the development of this cancer. Recently, some reports demonstrated that AR gene mutations were detected in human prostate cancer tissues. We have previously reported that one of eight endocrine therapy‐resistant prostate cancer cases showed AR gene mutation [Suzuki] et al: J Steroid Biochem Mol Biol46:759‐76, 19931. To further investigate structural abnormality of the AR in a large number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
103
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(104 citation statements)
references
References 20 publications
1
103
0
Order By: Relevance
“…To avoid this difficulty, we have introduced a modified Cre-loxP system to selectively introduce a point mutation into the AR LBD in the prostates of adult mice (AR pe-T877A/Y mice). This mutation (T877A) is often seen in prostatic tumors of androgenindependent patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this difficulty, we have introduced a modified Cre-loxP system to selectively introduce a point mutation into the AR LBD in the prostates of adult mice (AR pe-T877A/Y mice). This mutation (T877A) is often seen in prostatic tumors of androgenindependent patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…As the hydrophobic pocket in the LBD specifically recognizes and captures androgens and AR ligands, the mutated amino acid residues in the LBD, particularly in the motifs constituting the pocket, are presumed to impair specificity in hormone/ligand recognition. Indeed, in in vitro cell cultures, such human (h)AR point mutants display acquired responsiveness to other steroid hormones and androgen antagonists (17,18). The point mutation threonine 877 to alanine (T877A) in the LBD is one of the most common mutations in prostate tumors (15,16).…”
mentioning
confidence: 99%
“…In spite of the initial repressive effects, essentially all prostate cancers escape from antiandrogen therapy. In some of these hormone refractory tumours, a hot-spot AR mutation (Thr 877 → Ala; T877A) has been reported [12,13]. The mutation, which was initially detected in the prostate tumour cell line LNCaP [14], strongly affects AR steroid binding characteristics and its response to a variety of non-androgenic hormones and antiandrogens [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, in most of the studies, only a low frequency of mutations has been observed in the advanced-stage cancers or even in the hormone-refractory recurrent prostate cancers. 14,15 The association between the progression and AR expression or mutations of the AR gene is still not well defined. In the present study, we evaluated the prognostic significance of AR expression and AR gene mutations in 42 cases.…”
Section: Introductionmentioning
confidence: 99%